Toolkit for stabilizing the financial and economic state of construction participants in cyclical fluctuations - BIELIENKOVA, Olha; PALAHITSKYI, Viktor (Ways to Improve Construction Efficiency, 2026)
The article examines the issues of forming and implementing a system of anti-cyclical measures to stabilize the financial and economic state of construction participants in conditions of cyclical fluctuations in the economy. It is substantiated that the construction industry is one of the most vulnerable sectors of the economy, as it combines significant capital intensity, a long investment and production cycle and high dependence on the macroeconomic environment. This necessitates the development of a systemic approach to managing financial and economic stability both at the level of construction enterprises and at the level of individual investment and construction projects.The paper proves the feasibility of a hierarchical approach to anti-cyclical management, which involves coordinating strategic decisions at the enterprise level with operational measures implemented within specific projects. At the level of a construction enterprise, anti-cyclical measures are considered as an element of financial, investment and risk policy aimed at maintaining solvency, liquidity, financial balance and optimization of the project portfolio in accordance with the phases of the economic cycle. At the level of an investment and construction project, these measures are specified in the form of cash flow management, control of the estimated cost, minimization of project risks, ensuring calendar and network stability and maintaining investment attractiveness.A logical model of coordination of anti-cyclical measures is proposed according to the principle of "investment and construction project → construction enterprise", which is based on the vertical integration of management decisions and the presence of feedback information links. Such a model allows for timely adjustment of project implementation parameters and the structure of the enterprise’s portfolio depending on changes in the external economic environment, reducing the likelihood of accumulation of financial risks and preventing crisis phenomena in the activities of construction participants.The implementation of a coordinated system of anti-cyclical measures contributes to increasing the adaptability of investment and construction activities, reducing the negative impact of economic downturns and creating the prerequisites for ensuring financial stability and sustainable development of construction enterprises in conditions of economic instability.